Homestay programme as a Malaysian tourism product - Kayat, Kalsom (UUM press, 2011)
This book discusses the homestay programme in Malaysia in the context of tourism product.It begins by looking into the evolution of tourism in Malaysia, focusing on its growth and development.Tourism product is an important component of any tourism destination, thus the book later looks into the product concept as well as the development of tourism products in Malaysia.Malaysia has many natural, cultural and man-made tourist products and attractions that can potentially pull tourists to its shore.The rest of the book then turns into the discussion of the Malaysian homestay programme.The programme, which can be categorized as Malaysia’s rural cultural tourism product may well be a way to reinvigorate tourism as it is an initiative to attract alternative tourist markets due to its unique product elements.Different perspectives and conceptual frameworks are used in looking at the homestay programme specifically in the area of product benefits, tourist experience, resident perceptions, and product quality. The elements of the programme are identified and the outcomes explored.Finally, issues surrounding the programme are discussed and recommendations on future management of the programme are offered. The book is hoped to answer enquiries about the unique homestay programme in Malaysia, if not completely, at least partially.